2022
DOI: 10.3389/fpubh.2022.879698
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Differences in the Health Expenditure Efficiency of China: Reflections Based on the Background of the COVID-19 Pandemic

Abstract: The outbreak of the COVID-19 pandemic has brought several challenges to China's national health services, causing great risks and uncertainties to people's lives. Considering China's huge population and relatively small medical investment and its good performance in the COVID-19 pandemic, this research utilizes the hybrid meta-frontier model to analyze health expenditure efficiencies of 30 provinces in China from 1999 to 2018 and compares spatial and temporal differences of the efficiencies in regards to regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Insufficient or inefficient spending on public health reduces the health of citizens, which in turn slows down the process of economic development ( 1 ). The outbreak of the COVID-19 pandemic has had a great impact on the public health system of countries, seriously threatening the lives of many people ( 2 ). Therefore, in the context of COVID-19 ravaging the world, how to effectively improve health system efficiency and protect people's health has become a major issue that needs to be solved urgently.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient or inefficient spending on public health reduces the health of citizens, which in turn slows down the process of economic development ( 1 ). The outbreak of the COVID-19 pandemic has had a great impact on the public health system of countries, seriously threatening the lives of many people ( 2 ). Therefore, in the context of COVID-19 ravaging the world, how to effectively improve health system efficiency and protect people's health has become a major issue that needs to be solved urgently.…”
Section: Introductionmentioning
confidence: 99%
“…For economic performance, we use the economic growth factor indicated via gross domestic growth (GDP), governance or institutional quality is captured by regulatory quality (RQ), and government effectiveness. Besides, Domestic general government health expenditures (GHE) are also examined in the empirical model (18). Data for these variables are obtained from multiple sources, covering the 1996Q1 to 2020Q4 period for low-income countries 1 .…”
Section: Methodsmentioning
confidence: 99%
“…According to UNICEF estimates, 258,000 people died in Africa in 2017 because of air pollution. Following the COVID-19 pandemic, researchers have focused their attention on the impact of air pollution on viral movement (15)(16)(17)(18)(19)(20). Recent studies have also found a link between air pollution and COVID-19 pandemic related deaths and between air pollutants and human disease transmission (15,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, a 1% increase in the environmental regulation index raises the level of industrial green development by 0.0855%. This is because the expansion of fiscal decentralization helps to improve public sector efficiency and promotes government attention to environmental governance issues, which in turn increase green total factor productivity (Adam et al, 2014;Ma et al, 2021;Shi et al, 2022). When the level of fiscal decentralization is low, local governments have less autonomy to promote industrial green development through proactive environmental management.…”
Section: Threshold Effect Of Fiscal Decentralizationmentioning
confidence: 99%